Pengaruh Kualitas Layanan dan Fasilitas terhadap Kepuasan Pelanggan pada Perusahaan Bus PO. Gumarang Jaya - Havest Rizky R; Syahril Daud (Journal Of Business, Finance, and Economics (JBFE), 2024)
Consumer satisfaction can be created when passengers' expectations of the company's services meet or exceed them. The aim of the research carried out was to determine the influence of service quality and facilities on customer satisfaction at PT Gumarang Jaya. The research method used is quantitative research. The research location chosen was PT Gumarang Jaya. The distribution of members of the research population is PO.Gumarang Jaya Bus passengers and 150 people were selected as a sample. Data was collected through a questionnaire guided by a scale of 1-5. The data were analyzed using multiple linear regression analysis with the help of the SPSS Version 25.0 application. The results of research on the service quality variable obtained a value of tcount (5.851) > ttable (1.99) so that H0 was rejected. Then the results of the analysis on the facility variable obtained a value of tcount (5.612) > Ttable (1.99) so that Ho was rejected. The research conclusion is that service quality (X1) has a significant effect on customer satisfaction (Y) of PO.Gumarang Jaya buses. Facilities (X2) have a real influence on customer satisfaction (Y) of PO.Gumarang Jaya buses